Traços quantitativos e abundância de drosofilídeos como indicadores de impacto ambiental em fragmentos de floresta estacional semidecidual - Penariol, Leiza Viola [UNESP] (2012)
Loss of habitat is the main threat to biodiversity. This transformation is important to avoid losses and to manage the use of the remaining biodiversity. The genus Drosophila flies are considered bioindicators. Morphometric traits in drosophilids have been linked with the adaptive value of such bodies. This study evaluated the drosophilid assembly in forest fragments with different areas, using plenty of bio-indicator species, ecological parameters of these populations and analysis of three morphometric traits (wing length, width and length of the chest). Ten fragments of seasonal forest were sampled in border areas, indoor and through an inside edge-transect. The morphometric traits Zaprionus indianus and Drosophila simulans have been analyzed in four areas of study. In total 33.578 drosophilids were collected, distributed in 17 species, plus the Cardini and full groups and the saltans subgroup. Species drosophilids invaders such as Z. indianus, and D. simulans showed higher with smaller fragments, while native species D. willistoni occurred with greater abundance in the areas of greater extent. It has been estimated the value of 60 meters to the edge. Regarding morphometric measures, more stable environments, such as larger fragments, would have better conditions for the development of flies compared to impacted areas, such as smaller fragments, which occurs less resource availability and increased competition. This study corroborated this data to D. simulans, however, to Z. indianus the most important factor in the change was not the area of the fragment, it is likely that this species paras other factors such as the type of vegetation, are more decisive for body development